Brand Credibility and Customer-Based Brand Equity in Mobile Health Applications - Puspo Dewi Dirgantari; Yusuf Murtadlo Hidayat; Masharyono Masharyono (Business Education Program of Universitas Pendidikan Indonesia, 2023)
By comparing brand credibility (BC) and customer-based brand equity (CBBE), this study aims to establish a strong brand for health mobile applications in Indonesia. In-depth and extensive literature searches were used to perform the study, along with the distribution of questionnaires. 200 persons made up the samples that were collected. The technique is convenience-based (convenience sampling) and uses a Likert scale. To assess the data, structural equation modeling was employed. The findings indicate that brand power is fairly high among Indonesian consumers of health mobile applications. The BC variable influences CBBE. The greatest factor in the creation of CBBE is the Brand Performance component.